Sudan : Interim Poverty Reduction Strategy Paper-Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2013)
This Joint Staff Advisory Note focuses on the Interim Poverty Reduction Strategy Paper (I-PRSP) for Sudan. I-PRSP provides a useful stock taking of the socioeconomic situation in Sudan and offers a good basis for the design and monitoring of growth and poverty reduction policies. It is the first comprehensive policy document that assesses the challenges of and opportunities for poverty reduction. This strategy lays out a clear policy approach for the Government of Sudan to accelerate poverty reduction and provides a foundation for a roadmap to a full PRSP, but timelines and concrete next steps need to be urgently defined.